2022
DOI: 10.1002/jat.4420
|View full text |Cite
|
Sign up to set email alerts
|

Influences of repeated exposure to low levels of TiO2 nanoparticles on Kruppel‐like factors in 3D Caco‐2 spheroids and mouse intestines

Abstract: Kruppel‐like factors (KLFs) are a set of transcription factors (TFs) involved in the regulation of many basic biological processes, and recent studies suggested that nanoparticles (NPs) were capable to change KLFs in different models even at non‐cytotoxic concentrations. In this study, we repeatedly exposed 3D Caco‐2 spheroids and mice to TiO2 NPs, one of the most frequently used metal oxide NPs, and investigated the changes of KLF‐signaling pathways based on RNA‐sequencing. Although the internalization of TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…For example, we recently found that titanate nanofibers activated KLF6‐ATF3‐CCL2 signaling pathway, but RNAi revealed that KLF6 only directly regulated ATF3 in endothelial cells 68 . Nevertheless, the results from this study indicated that MoS 2 materials could activate KLF4‐signaling pathways both in vitro and in vivo, consistent with our recent observations in TiO 2 nanoparticle‐exposed intestines 25 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For example, we recently found that titanate nanofibers activated KLF6‐ATF3‐CCL2 signaling pathway, but RNAi revealed that KLF6 only directly regulated ATF3 in endothelial cells 68 . Nevertheless, the results from this study indicated that MoS 2 materials could activate KLF4‐signaling pathways both in vitro and in vivo, consistent with our recent observations in TiO 2 nanoparticle‐exposed intestines 25 …”
Section: Discussionsupporting
confidence: 91%
“…68 Nevertheless, the results from this study indicated that MoS 2 materials could activate KLF4-signaling pathways both in vitro and in vivo, consistent with our recent observations in TiO 2 nanoparticle-exposed intestines. 25 In summary, the results from this study showed that MoS 2 NSs or bulk reduced bodyweights of mice and increased organ coefficients, indicating the in vivo toxicity of these materials. The oral toxicity of MoS 2 NSs and bulk could be explained by that these materials T A B L E 1 The levels of trace elements in mouse intestines.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Several groups have developed 3D Caco-2 spheroids by seeding Caco-2 cells in ultralow attachment tissue culture materials. 82 Newer developments in 3D gut studies have emerged by implementing intestinal tissues from patients because they more closely mimic the human intestinal epithelium. 3D gut organoids are particularly advantageous and of interest because they encompass all intestinal cell types.…”
Section: Experimental Models To Study Nanoparticles' Transport Mechan...mentioning
confidence: 99%
“…Intestinal epithelial cells can also be grown into a 3D, spheroid conformation to represent the morphological geometry of the gut. Several groups have developed 3D Caco-2 spheroids by seeding Caco-2 cells in ultralow attachment tissue culture materials . Newer developments in 3D gut studies have emerged by implementing intestinal tissues from patients because they more closely mimic the human intestinal epithelium.…”
Section: Experimental Models To Study Nanoparticles’ Transport Mechan...mentioning
confidence: 99%